Myths in Online Dating’s Hodiernal Expressions - Tatan Tawami; Retno Purwani Sari (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2026)
This research aims to decode the sign system encoded in online dating hodiernal expressions. The decoding process involves Barthes' semiotic analysis of myths, structured in expressions, which reveals the connotative meaning and code system underlying these expressions. A qualitative descriptive method was used to analyze the data. The signs were decoded using Barthes' semiotic code to reveal their denotative meaning, which was then expanded into connotative meaning and the code system to expose the myths embedded in the expressions. The findings suggested that the myths were constructed through relations among connotative meanings and code systems. Four of the five code systems were identified; the semantic code system was the majority code, creating connotative meanings, and the others were proaretic, cultural, and symbolic codes. From this research, it can be concluded that the encoded message in expressions carries not only their literal meaning but also their relation to the outside world, namely, their connotative meanings. Therefore, these findings are expected to facilitate the interpretation of all recognized signs, thereby making meaning-making easier. Keywords: Online Dating, Myths, Hodiernal Expressions, Connotative Meaning